Chemical Evolution of Nitrogen-based Compounds in Mozzarella Cheeses - Barone, Caterina; Barebera, Marcella; Barone, Michele; Parisi, Salvatore; Zaccheo, Aleardo; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2018)
This Brief evaluates the consequences of protein modifications in cheeses, with special emphasis on mozzarella cheeses. It explains the influence of biogenic amines on food quality and safety. As certain biogenic amines display a toxic potential to humans, considerable research has been undertaken in recent years to evaluate their presence in fermented foods, such as cheeses. This Brief summarizes how the presence of amines is influenced by different factors such as cheese variety, seasoning and microflora. The authors compare typical profiles of different products, e.g. ripe vs. unripe cheeses, focusing also on the different types of mozzarella cheeses. The Brief also introduces several analytical methods and simulation techniques, which are being used to evaluate the evolutive profiles of different selected molecules, protein aggregation, or proteolysis. .
Biogenic amines in cheeses: Types and typical amounts -- Evolutive Profiles of Caseins and Degraded Proteins in Industrial High-Moisture Mozzarella Cheeses. A Simulative Approach -- Evolutive Profiles of Caseins and Degraded Proteins in Industrial Low-Moisture Mozzarella Cheeses. A Simulative Approach -- Evolutive Profiles of Caseins and Degraded Proteins in Industrial Diced Mozzarella Cheeses. A Simulative Approach.
Keywords: Food science; Proteins .; Nutrition .; Security systems; Food Science; Protein Biochemistry; Nutrition; Security Science and Technology